Extraction, purification and macrophage stimulatory activity of polysaccharide isolated from leaves of Perilla frutescens BRITTON var. crispa - Kim, Yu Jeong; Hwang, Jung Soon; Kwon, Ki Han (Progress in Nutrition, 2019)
The crude polysaccharide portion of Perilla frutescens BRITTON var. crispa (PFB-1) was prepared by following steps, hot water extraction (PFB-0), decolorization with methanol reflux and ethanol precipitation. The PFB-1 was separated by anion-exchange column chromatography (fraction: PFB-1-0). Purified PFB-1-0-ii was obtained from gel permeation column chromatography purification steps of PFB-1-0. The PFB-1-0-ii was shown to be one polysaccharide with molecular mass of 10 kDa (kilodalton). PFB-1-0-ii consists of mannose, galactose and glucose as major sugars with 82.8% carbohydrate. Next, this study investigated the effects of PFB-0, PFB-1, PFB-1-0, and PFB-1-0-ii on macrophage stimulatory activity in primary macrophages. PFB-0, PFB-1, PFB-1-0 and PFB-1-0-ii increased macrophage cellular lysosomal enzyme activities. Among the samples tested, PFB-1-0-ii exhibited the highest macrophage lysosomal enzyme activities. The macrophage-stimulating activity was significantly enhanced during the purification step. The results support the utility of purified polysaccharide from Perilla as immunostimulatory activity agent.